Risk management in innovative pedagogical classrooms - Campos Flores, Freddy William; Zuloaga Cachay, Jose Fortunato; Fuentes Adrianzen, Denny John; Cueva Valdivia, Johnny (Universidad Ciencia y Tecnología, 2022)
The purpose of risk management is to protect the Information and Communication Technologies (ICT) equipment against possible internal and external security breaches. The risk assessment worked with the technique of documentary analysis regarding the risks associated with the installation and equipment of the AIP, also used the survey to collect information through a virtual questionnaire, which was applied to teachers’ DAIP in order that they can assess the risk management in relation to the sustainability of ICT equipment. This information made it possible to propose a plan, as well as an evaluation of the computer assets in secure areas and equipment security, obtaining high and very high-risk levels that compromise the functionality of the ICT infrastructure and consequently harm the educational service, so prevention measures were proposed to mitigate the adverse effects. Keywords: Computational vulnerability, risk management plan, equipment security.